Strategies for improving the poor performance of Sarawak Football Association / Muhamad Afzal Jahangir and Nidzam Adzhar Hashim - Jahangir, Muhamad Afzal; Hashim, Nidzam Adzhar (2018)
Association football or more commonly known as football or soccer is a team sport played between two teams of eleven players of each side with a spherical ball. Over 200 countries and dependencies played this sport and it makes this sport is the world’s most popular sport. The game of football is played on a rectangular field with a goal at each end. The object of the game is to score by getting the ball into the opposing goal. The players are not allowed to touch the ball by their hands or arms while it is in play. Only goalkeepers are allowed to touch the ball but only when within their penalty area. Other players mainly use their feet to strike or pass the ball, but they may also use their head or torso. The team that scores the most goals by end of the match wins the game. If the score level at the end of the match, either a draw is declared or the game goes into extra time or penalty shootout depending on the format of the competition. The laws of the game were originally codified in England by The Football Association in 1863. Association football is governed internationally by the Federation International of Football Association (FIFA). This football association also organizes World Cups for both men and women every four years. FIFA is an association governed by Swiss Law that founded in 1904 and based in Zurich and it also has 211 member associations.